Antecedents and consequences of brand tribes in sports organizations: the role of brand personality dimensions - Nagore, Carlos (2023)
Purpose – This study examines how the brand personality dimensions of a sports brand organization influence brand tribalism, and the subsequent effects of tribalism on three consumer behavioral responses: loyalty, WOM, and recruitment. Theoretical framework – We base our conceptualization of sports brand personality on Tsiotsou’s (2012) model of brand personality, with five dimensions: competitiveness, prestige, morality, authenticity, and credibility. The study also uses Taute and Sierra’s (2014) model of brand tribalism, with four dimensions: lineage, social structure, sense of community, and defense of the tribe. Design/methodology/approach – We present a theoretical model estimated using data from a sample of 1,662 soccer fans of Spanish LaLiga clubs. The model is estimated using the PLS algorithm. Findings – We show that brand morality, prestige, and competitiveness have a positive influence on brand tribalism, while brand credibility and authenticity have a negative or non-significant influence on tribalism. Our results also support the notion that sports brand tribalism encourages fans to be more loyal and to engage in more positive WOM and recruitment behaviors. Practical & social implications of research – Managers should focus on improving the perceived morality (sustainable and socially responsible behaviors), prestige, and competitiveness of the sports brand. Originality/value – We show which dimensions of a sports brand personality influence brand tribalism, and its subsequent behavioral effects. Keywords – Brand tribalism, Brand personality, Brand loyalty, Word-of-mouth, PLS modeling.